The Role of the Lessor s Tacit Hypothec and Accession as Common Law Protection Measures for Landowners in Solar Energy Power Purchase Agreements - Watermeyer, Peter (Department of Construction Economics and Management, 2025)
The demand for renewable solar energy in private businesses is becoming a key component in everyday operations given today's energy climate in South Africa. A hurdle in integrating solar energy into a private business is the capital outlay required by the landowner to install the necessary solar infrastructure. The renewable energy industry provides an alternative to private landowners, making the benefits of solar energy available without requiring any capital outlay to fund solar installations. These opportunities for private landowners are typically governed by Power Purchase Agreements (PPAs) between the landowner and the Independent Power Producer (IPP). The PPA provides the contractual relationship between the landowner and the IPP for the buying and selling of solar energy, respectively. The PPA also outlines the parameters between the landowner and the IPP specific to the site as well as the performance obligations of each party. Problems may arise if the IPP fails to comply with its performance obligations. This dissertation investigates the possibility of applying common law protection measures against the IPP, should the latter fail in specific performance obligations set out in the PPA. The study focuses specifically on two common law protection measures, namely the lessor's tacit hypothec and the law of accession. The study has the following objectives: 1. Determine the legal criteria to rely on the lessor's tacit hypothec and accession respectively; 2. Investigate how the principles of the lessor's tacit hypothec can be utilised as a protection measure for landowners against non-performing IPPs in the context of a PPA; and 3. Investigate to what extent landowners can rely on the law of accession as an alternative protection measure against non-performing IPPs where the lessor's tacit hypothec is not a viable legal option. Following a multiple case-study approach, PPAs provided by participating IPPs are reviewed to determine to what extent the PPAs address issues relevant to the application of the lessor's tacit hypothec and accession. Furthermore, research participants are interviewed to collect data on the technicalities regarding the method of attachment of the solar infrastructure to the landowner's property as well as the general life span of these solar systems in relation to the PPAs signed by both parties. The study also identifies the challenges in the application of the two protection measures in the context of a PPA. The findings illustrate that the provisions of each PPA must be considered when determining the possibility of applying these protection measures against the non-performing IPP. Each PPA is project-specific, creating subtle nuances to the PPA. These subtle differences may support or exclude the application of the two protection measures. The dissertation makes recommendations regarding issues that should be addressed in a PPA. It also highlights aspects for future research in this context.